A study on job satisfaction amongst the customs officers grade W8 in the internal taxes division, Kuching, Sarawak - Muang @ Muaz, bin Sabu (2002)
The purpose of this research is to study on job satisfaction of the Custom Officers Grade W8 in the Internal Taxes Division Kuching Sarawak. Data was collected through the used of questionnaire distributed to 38 Customs Officers Grade W8